2018
DOI: 10.1101/421404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex human gut microbiome cultured in anaerobic human intestine chips

Abstract: The diverse bacterial populations that comprise the commensal microbiota of the human intestine play a central role in health and disease, yet no method is available to sustain these complex microbial communities in direct contact with living human intestinal cells and their overlying mucus layer in vitro. Here we describe a human Organ-on-a-Chip (Organ Chip) microfluidic platform that permits control and real-time assessment of physiologically-relevant oxygen gradients, and which enables co-culture of living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…These findings demonstrate the usefulness of the Colon Chip as an in vitro tool for evaluation of mucus structure and function, which could advance our understanding of mucus physiology in disease contexts. Considering recent advances in bacterial co-cultures in intestinal microfluidic models 23,24,35,36 , this microfluidic Colon Chip lined by patient-derived colonic epithelial cells may also facilitate development of new therapeutics or probiotics that modulate the mucus barrier, as well as provide a novel testbed for personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate the usefulness of the Colon Chip as an in vitro tool for evaluation of mucus structure and function, which could advance our understanding of mucus physiology in disease contexts. Considering recent advances in bacterial co-cultures in intestinal microfluidic models 23,24,35,36 , this microfluidic Colon Chip lined by patient-derived colonic epithelial cells may also facilitate development of new therapeutics or probiotics that modulate the mucus barrier, as well as provide a novel testbed for personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, plate-based cultures of CD34+ cells cannot mimic these effects and they also have known limitations with respect to diffusion-limited exchange of oxygen and nutrients, as well as removal of waste and soluble inhibitory factors 21 . In contrast, when we fabricated BM Chips using microfluidic devices that contained embedded oxygen sensors 22 , we found that oxygen levels remained constant at ~ 75% of atmospheric levels over 3 weeks in the BM Chip, whereas oxygen levels in static fibrin gel co-cultures containing the same cells dropped precipitously to near anoxic levels within the first week ( Supplementary Fig. 2b).…”
Section: Continuous Myeloid and Erythroid Cell Proliferation And Diffmentioning
confidence: 88%
“…BM Chips with embedded oxygen sensors were created as recently described 22 . For static gel culture measurements, an oxygen sensor spot (PreSens Precision Sensing GmbH, SP-PSt3-NAU) was placed at the bottom of a 96 well flat bottom plate before cell seeding.…”
Section: Oxygen Measurementsmentioning
confidence: 99%
“…Importantly, the EACC system facilitates short term co-culture of commensal nano-anaerobes (B. anaerobes. Notably, a recent study using microfluidic chips reports the ability to co-culture Caco-2 and primary cell lines with anaerobic bacteria, specially Bacteroides fragilis 25 . While this is a major advancement in microfluidic systems, the dependency for using a specifically engineered chip for study limits throughput, increases the expense, and restricts the use of the system to specialist labs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a major limitation of these systems is the use of the Caco-2 cell line as opposed to a more physiologically-relevant cell culture model, such as human enteroids. Advancing on these systems, a recent study by Jalili-Firoozinezhad et al (2018) demonstrated the ability to co-culture anaerobic bacteria with human enteroids and maintain viability for up to 120 hours 25 . However, as with other microfluidics-based approaches, it is highly technical, labor-intensive, and proprietary.…”
Section: Introductionmentioning
confidence: 99%